The impact of automation of operational processes and its role in raising the competitiveness of the Aden Container Terminal - Aref Hasan Abdullah Al-Shabi; Osama Fawzy Ahmed Elbayoumi (Maritime Research and Technology)
Ports are an essential pillar of economic development globally, as they contribute significantly to enhancing local and international trade exchange. Ports seek to improve their efficiency and provide high-quality services to meet customer needs. Consequently, many countries have developed their maritime capabilities using ICT, which has increased trade volume, reduced overall costs, and reduced port arrival time for ships. Since its emergence, container transportation has become vital in the field of logistics and global trade, as it contributes significantly to improving the efficiency of supply chains by simplifying shipping and tracking processes using modern technology, and effectively enhances local and international trade exchange.   The study aims to understand the sources of weakness that affected the ability of the Aden Container Terminal to compete, and to provide future directions and suggestions for enhancing competitiveness through the application of technology and automation. The researcher used the descriptive analytical approach, where a questionnaire was created to measure the impact of automation of operational processes at the Aden Container Terminal, and this data was analyzed using the SPSS program.   Received: 03 June 2024 Accepted: 14 July 2024 Published: 19 August 2024